Parent-reported Mental Health Problems and Mental Health Services Use in South Australian School-aged Children - Jing Wu; Eleonora Dal Grande; Helen Winefield; Danny Broderick; Rhiannon Pilkington; Tiffany K Gill; Anne W Taylor (AIMS Press, 2016)
Background:Monitoring and reporting childhood mental health problems and mental health services utilization over time provide important information to identify mental health related issues and to guide early intervention. This paper aims to describe the recent prevalence of parent-reported mental health problems among South Australian (SA) children; to identify mental health problems associated characteristics; and to describe mental health services utilization and its related characteristics among this population. Methods:Parent-reported mental health problems were assessed against the first item of the Strength and Difficulties Questionnaire. School-aged children were randomly sampled monthly and data were collected using a surveillance system between 2005 and 2015. Associations between mental health problems and various factors were analysed using univariable analysis and multivariable logistic regression modelling. Results:Prevalence of parent-reported mental health problems among children was 9.1% and 9.3% for children aged 5 to 11 years and children aged 12 to 15 years, respectively. No change in prevalence was observed during the past decade. Mental health problems were associated with male sex, long-term illness or pain, negative school experiences, not living with biological parents, and living in a rental dwelling. Less than half (48.7%) of the children with mental health problems received professional help. An increasing trend was found in mental health services utilisation among children aged 5 to 15 years. Utilization of mental health services was associated with male sex, older age, long-term illness or pain, and feeling unhappy at school. Conclusion:This study reports the prevalence of parent-reported mental and mental health services utilisation among SA school-aged children. Identified characteristics associated with mental health problems and mental health services utilisation provide useful information for the planning of catered population initiatives.